Wolf, Canis lupus, Avoidance Behaviour of American Elk, Cervus elaphus, in Jasper National Park, Alberta - Dekker, Dick; Slatter, Greg (The Canadian Field-Naturalist, 2009)
An American Elk calf (Cervus elaphus) that was captured near human habitation in Jasper National Park, Alberta, was fitted with a radio-collar and released 40 km away in the park's main valley of the Athabasca River. The calf joined a local herd of elk, and its radio signal revealed that the elk, in two months' time, travelled eight times back and forth between the herd's traditional semi-open winter range at Devona and a largely wooded area at Rocky River >3 km away. Each time, on their trans-valley route the elk crossed a busy highway, a railway, and a partly frozen river. Sightings of elk and Wolves (Canis lupus) were inversely correlated on 97 days of observation at Devona. We conclude that the elk's migrations were prompted by their urge to avoid and flee from Wolves, which were common at both locations.